A Proterozoic Wilson cycle identified by Hf isotopes in central Australia: Implications for the assembly of Proterozoic Australia and Rodinia - Smits, R.; Collins, William; Hand, M.; Dutch, R.; Payne, J. (Geological Society of America, 2014)
Current models for the assembly of Proterozoic Australia suggest that the North Australian craton (NAC), West Australian craton (WAC), and South Australian craton (SAC) had amalgamated by at least 1.6 Ga, with possible rafting and reattachment of the SAC by ca. 1.3 Ga. In this scenario, the younger (1.2-1.1 Ga) Grenvillian-aged Musgrave Province of central Australia, which separates all three cratons, has been considered postcollisional to intracratonic. However, new and recent U-Pb and Lu-Hf isotopic analyses of zircons from the Musgrave Province indicate continuous active-margin magmatic activity between 1.7 and 1.2 Ga. A distinctive inverted U-shaped pattern of the Hf array for this 500 m.y. period is evidence of part of a Proterozoic Wilson cycle, with subduction initiation at 1.7 Ga and eventual ocean closure by 1.2 Ga. We estimate that the cycle began at 2.2 Ga. Overlap of the Musgrave zircon age spectra and Hf isotopic array with the along-strike Albany-Fraser orogen (AFO) suggests derivation of the Musgrave Province from the WAC, not the NAC or SAC as previously thought. The Musgrave Province link to the WAC confi rms that Australia did not assemble until at least early Grenvillian time (ca. 1.2 Ga). Moreover, because the SAC was part of the much larger Mawson continent, the 1.2 Ga collision was of transcontinental magnitude similar to that of the type-Grenville orogen in Laurentia. This favors an Australia-Mexico (AUSMEX) confi guration at 1.2 Ga, rather than the southwestern United States and East Antarctica (SWEAT) or Proterozoic Australia-western United States (AUSWUS) models. The Musgrave-AFO marks a major, underestimated phase of Rodinian assembly.